1991
DOI: 10.1152/ajpregu.1991.260.5.r906
|View full text |Cite
|
Sign up to set email alerts
|

TNF-induced anorexia and learned food aversions are attenuated by area postrema lesions

Abstract: Tumor necrosis factor (TNF) or cachectin has been proposed as an important mediator of cancer anorexia and cachexia. The present studies examined the extent to which TNF administration generates symptoms similar to those produced by tumor growth. Like the growth of certain tumors, TNF administration was found to be associated with the development of strong aversions to a novel diet. Area postrema lesions were found to significantly attenuate the effects of TNF on intake of a novel diet, a finding previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…For example, previously experienced foods are not rejected in SEA or SEB challenged mice, but new foods provided in a new environment result in significant reduction of intake (Kusnecov et al , 1999; Kawashima & Kusnecov, 2002; Rossi-George et al , 2005). Centrally, this was shown to be CRH-dependent (Kaneta & Kusnecov, 2005), and linked to TNFα production (Rossi-George et al, 2005), a finding consistent with evidence in rats that TNFα administration reduces food intake if the food is novel (Bernstein et al , 1991). Finally, due to the involvement of CRH and HPA axis activation, it was hypothesized that these behaviors might have involved increased levels of anxiety after SEA challenge.…”
Section: Introductionsupporting
confidence: 70%
“…For example, previously experienced foods are not rejected in SEA or SEB challenged mice, but new foods provided in a new environment result in significant reduction of intake (Kusnecov et al , 1999; Kawashima & Kusnecov, 2002; Rossi-George et al , 2005). Centrally, this was shown to be CRH-dependent (Kaneta & Kusnecov, 2005), and linked to TNFα production (Rossi-George et al, 2005), a finding consistent with evidence in rats that TNFα administration reduces food intake if the food is novel (Bernstein et al , 1991). Finally, due to the involvement of CRH and HPA axis activation, it was hypothesized that these behaviors might have involved increased levels of anxiety after SEA challenge.…”
Section: Introductionsupporting
confidence: 70%
“…sickness behavior) which include fatigue, malaise, depression, and anorexia. It has been shown that administration of recombinant TNF induces significant reduction in food intake both in rodents and in humans (Bernstein et al, 1991; Michie et al, 1989; Spiegelman and Hotamisligil, 1993). How TNF regulates food intake remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…How TNF regulates food intake remains incompletely understood. Both peripheral and brain mechanisms are likely involved (Bernstein et al, 1991; Dantzer, 2001; Plata-Salaman, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Exogenous administration of sublethal doses of TNF-· that do not cause signifi-320 Neuroimmunomodulation 1999; 6:319-329 Ando/Dunn cant hemodynamic changes has been reported to exert CNS effects such as activation of the hypothalamic-pituitary-adrenal HPA axis [3][4][5], fever [6,7], increasing slowwave sleep [8], and reducing food intake [9]. TNF-· can induce taste aversions [9] and decrease social exploration [10], components of sickness behavior. TNF-· has been suggested to be one of the mediators of the actions of endotoxin on the brain, such as HPA activation [11], and changes in body temperature [7].…”
Section: Introductionmentioning
confidence: 99%